Radiofrequency ablation of atypical cartilaginous tumors in long bones: a retrospective study - Ricardo Rivas (International Journal of Hyperthermia, 2019)
Purpose: To determine the size of the ablation zone after radiofrequency ablation (RFA) of atypical cartilaginous bone tumors (ACT) using temperature-controlled 20 and 30 mm RFA straight non-cooled electrodes. Materials and methods: Sixteen patients with ACT in their long bones, who had undergone a single-session single-application CT-guided temperature-controlled RFA, were included retrospectively in the study. Tumors with a diameter of 10–25 mm were treated with 20 mm electrodes (n = 10), and tumors of 25–35 mm, with 30 mm electrodes (n = 6). The ablated zone was measured after three months on MRI images. Results: All the tumors were within the ablated zone on the 3-month follow-up MRI scan. The mean ablation time with the electrode, at a target temperature of 90 °C, was 7.6 minutes (range 6–10). The median of the largest ablation diameters, on applying the 20 and 30 mm electrodes, were 42 mm (IQR 8.5, range 30–51 mm) and 44.5 mm (IQR 4.5, range 42–63 mm), respectively. Conclusions: All the retrospectively viewed tumors in the long bones of ACT patients treated with RFA were completely ablated. The ablation zone diameters in the bones were larger than expected, when compared to other tissues, such as the liver.